Peripheral muscle function during repeated changes of direction in professional soccer players - Rampinini, E.; Martin, M.; Ferioli, D.; Bosio, A.; Azzolini, M.; Riggio M.; Maffiuletti, N. A. (European Journal of Applied Physiology, 2022)
Purposes To evaluate peripheral muscle function of the knee extensors during repeated changes of direction in professional soccer players by examining differences between competitive levels, periods of the season and playing positions, and to investigate the relationships between peripheral muscle function and physical activities during matches.